Land acquisition practice in Malaysia / Zulaikha Binti Zailan - Zailan, Zulaikha (Faculty of Architecture, Planning and Surveying, 2015)
One of the jurisdiction section been applied in Malaysia is Land Acquisition Act 1960 and from public side it been negative expectation regarding this Act because this Act are approve any alienated land to be acquired in reasons to be develop for public interest. Without deep explanation regarding this Act, Mala fide in public side will be growth and the wrong concept are been applied to the public. In avoid any misunderstanding and biased, each person who involve in this situation should have some information and general knowledge regarding this matter. Not every aspects from this Act is cruel, there are some part in this Act are guide to the consider the humanity and the best solution offer by this Act are by make sure the proprietor get the inadequate compensation and certain thing which by Land administrator opinion can be paid to the landlord. Cannot be deny, the sentimental value are attach with the property, but back to the religion, there are nothing is own by us and everything is just the borrower from our Creator. This Act made for unrestraint the development sector in this country synonym with this country status as a developing country. The amendment in this Act still needed from time to time in make this Act are relevant to be use and suitable with the condition and current situation.